Aspirin is associated with reduced cartilage loss in knee osteoarthritis: Data from a cohort study. Issue 3 (July 2015) - Wluka, Anita E.; Ding, Changhai; Wang, Yuanyuan; Jones, Graeme; Urquhart, Donna M.; Cicuttini, Flavia M.
Graphical abstract: Highlights: Inflammation and vascular health may contribute to the progression of knee osteoarthritis. In a cohort of people with symptomatic knee osteoarthritis, use of low dose aspirin was protective of medial tibial cartilage loss over 2 years. Aspirin may play a role in the prevention and management of knee osteoarthritis. Abstract: Objectives: Aspirin, widely used in the prevention of cardiovascular disease, in low dose, has anti-inflammatory and vasculoprotective effects: both of these processes contribute to the pathogenesis of osteoarthritis. We examined whether use of low dose aspirin affects change in knee cartilage volume in osteoarthritis. Methods: Participants from the Melbourne osteoarthritis cohort were classified as users and non-users of aspirin, according to baseline use (≤300 mg/day). Their knees were imaged twice over 2 years. Tibial cartilage volumes were measured and change calculated. Results: Twenty one (18%) of 117 eligible participants were aspirin users. Annual change in medial tibial cartilage volume was −43 mm 3 (95% confidence intervals (CI) −93, 10) in aspirin users and −101 mm 3 (95% CI −125, −77) in non-users ( p  = 0.043 for difference) after adjusting for age, gender, BMI and radiographic severity. Similar results were seen for annual percentage loss (1.9% vs 5.4%, p  = 0.034). No difference was observed for lateral tibial cartilage change and annual change ( p  = 0.98, 0.87 respectively) Conclusion: Low dose aspirin use was associated with reduced medial tibial cartilage loss over 2 years in people with knee osteoarthritis. This data is hypothesis generating and clinical trials are required to confirm efficacy. If this hypothesis is confirmed, low dose aspirin may be used to reduce the progression of knee osteoarthritis.